A numerical study on non-premixed H2/air flame stability in a micro-combustor with a slotted bluff-body. (6th January 2021) - Li, Linhong; Fan, Aiwu
Abstract: A planar micro-combustor with a slotted bluff-body was developed for non-premixed H2 /air combustion. Numerical simulation was conducted and the flame blow-off limit under blockage ratio of ξ = 0.45, 0.55 and 0.64 was obtained (corresponding half height of the bluff-body is 0.25, 0.30 and 0.35 mm, total height of the channel is 1.1 mm). It was found that the blow-off limit peaks at ξ = 0.55. The simulation results of flame blow-off dynamics demonstrate that when the blockage ratio is small, the flame root cannot be anchored by the recirculation zone and the flame is entirely blown off the bluff-body. However, if the blockage ratio is relatively large, flame splitting occurs due to excess strain rate before flame being blown out. Analysis reveals that increasing the blockage ratio of the bluff-body has both positive and negative impacts. On the one hand, a large blockage ratio can increase the turbulence kinetic energy in the recirculation zone, which promotes fuel-air mixing and flame stability. On the other hand, the augmented stretch effect leads to local extinction and flame splitting. As a result, the combustor with a medium blockage ratio of the bluff-body can gain a tradeoff between the positive and negative aspects and achieve a largest blow-off limit. Graphical abstract: A planar micro-combustor with a slotted bluff-body was developed for non-premixed H2 /air combustion. It is found that increasing the bluff-body size has both positive and negative impacts. Therefore, a medium blockage ratio can gain a tradeoff between the positive and negative aspects and achieve the largest blow-off limit. Image 1 Highlights: A micro-combustor with slotted bluff-body was designed for non-premixed H2 /air flame. Effect of bluff-body blockage ratio on flame blow-off limit was numerically studied. The flame blow-off limit peaks at a medium blockage ratio of the bluff-body. Increasing the blockage ratio of bluff-body has both positive and negative impacts. A medium blockage ratio gains a tradeoff between the positive and negative effects.